Corporate Board Characteristics and Deposit Money Banks (DMBs) Performance in Nigeria for the period 2008-2017 - Nwanne, T. F. I.; Okonkwo, E. J. (Archives of Business Research, 2019)
The study investigates empirically the corporate board characteristics and Deposit Money Banks (DMBs) performance in Nigeria for the period 2008-2017. It is motivated by the lack of confidence by investors in the capital market, the persistent agency problems, and the insolvency of large firms such as banks. The general objective of this study is to investigate the impact of corporate board characteristic on DMBs financial performance in Nigeria. Four research models/hypotheses were formulated based on the literature reviewed and also considered are the important factors affecting the performance of DMBs in the Nigerian banking industry. This study investigated three of the listed DMBs using a simple Judgmental Sampling Technique in a period of ten years each 2008 to 2017. The population of the study is made up of all the 21 DMBs listed in the Nigerian Stock Exchange as at 2019. The data collected for the research were analyzed with econometric e-view. The panel data was further analyzed using the random effect model. We found that board skill shows a positive and significant relationship with profit for the year, among others. The implication of our findings is that each DMBs studied are not adequately implementing the corporate governance practices, hence, the reasons for the negative impacts of the independent variables except in the case of board qualification. Hence, we recommend that critical attention should be given to corporate governance practices especially the CBN corporate governance codes for a better performance in the Nigeria banking industry.